Carboranyl-1,8-naphthalimide intercalators induce lysosomal membrane permeabilization and ferroptosis in cancer cell lines - Sebastian Rykowski; Dorota Gurda-Woźna; Agnieszka Fedoruk-Wyszomirska; Marta Orlicka-Płocka; Aleksandra Kowalczyk; Paweł Stączek; Marta Denel-Bobrowska; Katarzyna Biniek-Antosiak; Wojciech Rypniewski; Eliza Wyszko; Agnieszka B. Olejniczak (Taylor & Francis Group, 2023)
The synthesis of carborane-1,8-naphthalimide conjugates and evaluation of their DNA-binding ability and anticancer activity were performed. A series of 4-carboranyl-3-nitro-1,8-naphthalimide derivatives, mitonafide and pinafide analogs, were synthesised via amidation and reductive amination reactions, and their calf thymus DNA (ct-DNA)-binding properties were investigated using circular dichroism, UV-vis spectroscopy, and thermal denaturation. Results showed that conjugates 34-37 interacted very strongly with ct-DNA (ΔTm = 10.00-13.00 °C), indicating their ability to intercalate with DNA, but did not inhibit the activity of topoisomerase II. The conjugates inhibited the cell growth of the HepG2 cancer cell line in vitro. The same compounds caused the G2M phase arrest. Cell lines treated with these conjugates showed an increase in reactive oxygen species, glutathione, and Fe2+ levels, lipid peroxidation, and mitochondrial membrane potential relative to controls, indicating the involvement of ferroptosis. Furthermore, these conjugates caused lysosomal membrane permeabilization in HepG2 cells but not in MRC-5 cells.